1926 Mass. Acts 256, An Act Prohibiting the Sale and Use of Silencers for Firearms - (:unkn) unknown (General Publisher, 1926)
Whoever sells or keeps for sale, or offers, or gives or disposes of, or uses, any instrument, attachment, weapon or appliance for causing the firing of any gun, revolver, pistol or other firearm to be silent or intended to lessen or muffle the noise of the firing or any gun, revolver, pistol or other firearm shall be punished by imprisonment for not more than five years in the state prison or for not more than two and one half years in a jail or house of correction.
--
Keywords: SUPPRESSORS